2009
DOI: 10.1086/605430
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Programs for Infants, Children, Adolescents, and Adults: Clinical Practice Guidelines by the Infectious Diseases Society of America

Abstract: Evidence-based guidelines for immunization of infants, children, adolescents, and adults have been prepared by an Expert Panel of the Infectious Diseases Society of America (IDSA). These updated guidelines replace the previous immunization guidelines published in 2002. These guidelines are prepared for health care professionals who care for either immunocompetent or immunocompromised people of all ages. Since 2002, the capacity to prevent more infectious diseases has increased markedly for several reasons: new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(86 citation statements)
references
References 65 publications
0
81
0
5
Order By: Relevance
“…It is possible that, for this population, alternative venues such as schools would be appropriate. [17][18][19] Results from our review of NIS-Teen data provide a glimpse into provider practices and identify several areas for improvement. Vaccination coverage could have been Ͼ80% for Td/ TdaP and MenACWY and as high as 74% for the first dose of HPV had providers taken advantage of existing vaccination visits and administered all indicated vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that, for this population, alternative venues such as schools would be appropriate. [17][18][19] Results from our review of NIS-Teen data provide a glimpse into provider practices and identify several areas for improvement. Vaccination coverage could have been Ͼ80% for Td/ TdaP and MenACWY and as high as 74% for the first dose of HPV had providers taken advantage of existing vaccination visits and administered all indicated vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Administering all indicated vaccines during the same visit is a recommended standard of child and adolescent immunization 20 and is endorsed by numerous professional organizations. [17][18][19] Efforts at the practice level should focus on removing the barriers that prevent providers from offering simultaneous vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…We used Poisson regression with robust variance to estimate overall and subgroup-specific (i.e., by age group, racial/ethnic group, and insurance subgroup given evidence of potential differences in vaccine uptake by these factors) 11,12 HPV and influenza vaccination prevalence ratios (PR) and corresponding 95% confidence limits (CL) 13 comparing females whose parents were informal caregivers with females whose parents were not informal caregivers. We identified a minimal sufficient set of covariates for adjustment to reduce confounding bias using the back-door criterion in a directed acyclic graph.…”
Section: Discussionmentioning
confidence: 99%
“…Limited access to immunizations has been identified as one of the primary barriers to adult immunization. 32 One study reported that alternative locations for immunization, such as the workplace, can successfully address the issue of inconvenience in the vaccination decision. 33 Parents visit the pediatric office frequently with their infants and young children, where most vaccines needed for immunization of both children and adults are available.…”
Section: Potential Benefits and Concerns Of Immunizing Parents In Thementioning
confidence: 99%